2021
DOI: 10.3390/languages6020096
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Accent in Pre- and Primary School Heritage Bilinguals

Abstract: Previous research has shown that the two languages of early bilingual children can influence each other, depending on the linguistic property, while adult bilinguals predominantly show influence from the majority language to the minority (heritage) language. While this observed shift in influence patterns is probably related to a shift in dominance between early childhood and adulthood, there is little data documenting it. Our study investigates the perceived global accent in the two languages of German-Russia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…In line with previous research, including recent studies on vocabulary acquisition in RHL (e.g., Klassert et al, 2014), we also see in Figure 4 that the two lines for HL and majority language development cross around age 5 for the children from families with two Russian-speaking parents, indicating that the dominance shift occurs already at this young age in this group of RHL children. This finding is compatible with the reversed accentedness pattern that we observed in an earlier study with the same group of German-Russian bilinguals, where the incidence of a perceived foreign accent decreased from younger (preschool) to older (primary school) children in German, while it increased for Russian (Kupisch et al, 2021). While no such shifts have been attested in our previous studies investigating the acquisition of grammatical gender in RHL in the same participant groups, it is clear that all three linguistic domains are affected by input factors, with language exposure in the home in terms of family type (HR family vs. mixed family) and age of starting preschool as the major predictors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous research, including recent studies on vocabulary acquisition in RHL (e.g., Klassert et al, 2014), we also see in Figure 4 that the two lines for HL and majority language development cross around age 5 for the children from families with two Russian-speaking parents, indicating that the dominance shift occurs already at this young age in this group of RHL children. This finding is compatible with the reversed accentedness pattern that we observed in an earlier study with the same group of German-Russian bilinguals, where the incidence of a perceived foreign accent decreased from younger (preschool) to older (primary school) children in German, while it increased for Russian (Kupisch et al, 2021). While no such shifts have been attested in our previous studies investigating the acquisition of grammatical gender in RHL in the same participant groups, it is clear that all three linguistic domains are affected by input factors, with language exposure in the home in terms of family type (HR family vs. mixed family) and age of starting preschool as the major predictors.…”
Section: Discussionsupporting
confidence: 92%
“…Large-scale investigations studying RHL development across a wider age range and a larger number of children are scarce. To fill in this gap, in the current study, we investigate heritage language development in preand primary-school children between the ages of 3 and 10 based on data obtained in a large-scale project focusing on the grammatical and phonological (global accent) development in RHL in Norway, Germany, and the United Kingdom (UK) (Mitrofanova et al, 2018(Mitrofanova et al, , 2022Rodina et al, 2020;Kupisch et al, 2021). 1 The in-depth investigation of grammatical gender in these studies revealed that bilinguals in different national contexts developed finegrained sensitivity to grammatical gender cues in Russian, which ensured their successful acquisition of this property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are more dominant in their SL German than in their HL Portuguese (see Figures 1 and 2). This finding is in line with the literature on HL development, which assumes a switch to the dominant SL as soon as child HSs enter the SL's school system (Benmamoun et al, 2013;Kupisch et al, 2021;Rothman, 2009). Our results indicate that the effect of this switch lasts over the HSs' lifetime if they maintain their residence in the migration setting.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 91%
“…For bilingual children, in particular for child HSs, it is assumed that a significant change in language balance occurs when entering the school system, particularly when the main language of instruction is the SL (Benmamoun et al, 2013;De Cat, 2020). For instance, in a study on global accent in German-Russian bilingual children living in Germany (with Russian as HL and German as SL), Kupisch et al (2021) compared preschool with primary school children and concluded that a significant change in their accent occurred in this age span. The authors argue that this may be the consequence of quantitative and qualitative changes in language exposure (maybe also in language attitudes), and be indicative of changes in language dominance toward the dominant SL (German).…”
Section: Measuring Language Dominancementioning
confidence: 99%